Assessment of the Beneficial Impacts of Water-Induced Gully Erosion in Eastern Nigeria - Igwe, P. U. (Journal of Sustainability and Environmental Management, 2024)
Water-induced gully erosion, an extreme form of soil erosion, leaves a conspicuous and easily observable mark on the land, representing a significant challenge to the environment and communities worldwide. While its detrimental environmental and socio-economic impacts have been extensively studied, its potential benefits have often been overlooked. Therefore, this study aimed to investigate the beneficial impacts of gully erosion in Eastern Nigeria, a region known for its susceptibility to this phenomenon. The region comprises nine areas at high risk of gully erosion, each located in one of its constituent states, which were purposefully selected for the study. A community located near a large gully was conveniently sampled from each of these nine areas. A total of 399 household heads residing within 0.3km (300m) radius of the gullies’ head-scrapes were purposively sampled, out of which 370 completed and returned the questionnaires. The research employed various data collection methods, including questionnaires, interviews, observations, photographs, and satellite imagery. Respondents were asked to indicate their agreement with statements using a five-point Likert scale: strongly agree (5), agree (4), neutral (3), disagree (2), and strongly disagree (1). Data were analyzed using the Chi-square (X2) test in SPSS, version 22.0. The results revealed that self-employment in sand mining activities, such as loaders, beach owners, food sellers, and buyers and sellers of sand, was the most significant benefit, while the use of sand as a raw material for glass industries was perceived as the least beneficial. There was a significant difference in the mean ratings among the affected people regarding the benefits of gully erosion in the region (X2 value= 997.933, p = 0.00, p < 0.05 significant level). The study’s recommendations include maximizing the benefits of sand mining businesses and establishing tourist centers around stabilized gullies and lakes created by gullies in the region, among others.